2014
DOI: 10.1111/sjop.12184
|View full text |Cite
|
Sign up to set email alerts
|

Action orientation overcomes the ego depletion effect

Abstract: It has been consistently demonstrated that initial exertion of self-control had negative influence on people's performance on subsequent self-control tasks. This phenomenon is referred to as the ego depletion effect. Based on action control theory, the current research investigated whether the ego depletion effect could be moderated by individuals' action versus state orientation. Our results showed that only state-oriented individuals exhibited ego depletion. For individuals with action orientation, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Moreover, an experimental study showed that action‐oriented people—compared with state‐oriented people—were quicker to mentally disengage from the devitalizing impact of a demanding situation (Schlinkert & Koole, in press, Study 2). These findings fit with the idea that action‐oriented people can draw upon a superordinate process of volitional control to insulate themselves from the depleting effects of demanding conditions (see also Dang, Xiao, Shi, & Mao, ; Gröpel, Baumeister, & Beckmann, ; Jostmann & Koole, ; see Koole et al, , for a review).…”
Section: The Empirical Domains Of Internalization Vitality and Flowsupporting
confidence: 73%
“…Moreover, an experimental study showed that action‐oriented people—compared with state‐oriented people—were quicker to mentally disengage from the devitalizing impact of a demanding situation (Schlinkert & Koole, in press, Study 2). These findings fit with the idea that action‐oriented people can draw upon a superordinate process of volitional control to insulate themselves from the depleting effects of demanding conditions (see also Dang, Xiao, Shi, & Mao, ; Gröpel, Baumeister, & Beckmann, ; Jostmann & Koole, ; see Koole et al, , for a review).…”
Section: The Empirical Domains Of Internalization Vitality and Flowsupporting
confidence: 73%
“…Finally, the current analysis also sheds light on mechanisms underlying individual differences in vulnerability to ego depletion. For instance, recent studies found that action-oriented individuals (vs. state-oriented individuals) could successfully overcome ego depletion (Dang, Xiao, Shi & Mao, 2015;Gr€ opel, Baumeister & Beckmann, 2014). Action orientation has been linked to effective goal maintenance under demanding situations (Jostmann & Koole, 2007), and our results may be taken to suggest that actionoriented individuals get over ego depletion through a powerful goal maintenance mechanism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Self-control can also be regarded as the ability of higher-order functions to modulate the activity of lower-level functions, where higher-order functions manifest themselves externally in complex behavior, adjusted according to the environmental needs, while lower-level functions are manifested in simple and stereotyped behaviors, not adjusted according to the demands of the environment (Roskies, 2010a ). Everyone exhibits a different degree of self-control compared to other individuals, and for each person the degree of self-control varies over time (Baumeister et al, 2006 ; Casey et al, 2011 ; Dang et al, 2015 ). The variability of self-control that is manifested in behavior and can be measured with the test has its base in neuronal functioning, which in turn depends on education and habits, external circumstances and the internal neuronal noise.…”
Section: Operazionalizing Measuring and Verifying: From The Action Tmentioning
confidence: 99%